Flexible Modules Using <70 μm Thick Silicon Solar Cells. (August 2016) - Augusto, André; Tyler, Kevin; Herasimenka, Stanislau Y.; Bowden, Stuart G.
Abstract: Highly flexible modules using thin 153 cm 2 silicon crystalline cells and transparent fluoropolymer foil are demonstrated. The modules can be flexed 200 times around a bend radius of 4 cm without change in efficiency. The silicon crystalline heterojunction solar cells are 65±5 μm-thick with efficiencies up to 18.4%. Cracks in the solar cells and interconnections that are induced by mechanical stress during module bending are examined using electroluminescence. Two interconnection solutions are discussed: ribbons affixed to the busbars using a conductive adhesive, and indium coated wires directly bonded to the cell fingers. Modules using wire interconnection are found to be highly flexible with efficiencies greatly exceeding existing commercial flexible modules using thin films and have potential applications in light-weight modules for building integrated and portable photovoltaic power.